2022
DOI: 10.3389/frsus.2022.924926
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Demolition Waste Management: A Systematic Scoping Review of Risks to Occupational and Public Health

Abstract: Despite the relatively benign characteristics of construction and demolition waste, its mismanagement can result in considerable harm to human health for 200 million workers and those who live and work in proximity to construction and demolition activities. The high number of workers classified as informal, results in a large unregulated and vulnerable workforce at a high risk of exposure to hazards. We focused a systematic scoping review (PRISMA-ScR) on evidence associating construction and demolition waste w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Managing hazardous materials in C&D waste is vital in order to avoid fines and environmental liabilities. 39,40…”
Section: Construction Wastementioning
confidence: 99%
“…Managing hazardous materials in C&D waste is vital in order to avoid fines and environmental liabilities. 39,40…”
Section: Construction Wastementioning
confidence: 99%
“…Further it has been shown that agriculture, gardening, fishing and road construction in which exposure to wet soil occurs act as risk factors for melioidosis infection [18]. In low and middle income countries including India, large unregulated vulnerable workforce exists in construction and demolition activities and hence risk mitigation is required [19]. Moreover the lack of awareness about melioidosis even among literate people augments the problem.…”
Section: Importance Of Melioidosis Surveillance In Indiamentioning
confidence: 99%
“…This issue is getting worse with the global trend of urbanization, which creates an insatiable demand for infrastructure and, consequently, concrete (Kabirifar et al, 2020;Rashid and Singh, 2023). The rise in demand has resulted in excessive aggregate usage, diminishing our natural resources (Cook, Velis and Black, 2022). Annual consumption of concrete has jumped to about 15 billion tonnes, with natural aggregates accounting for approximately 11 billion tonnes (Bui, Satomi and Takahashi, 2017).…”
Section: Introductionmentioning
confidence: 99%